NILAI-NILAI PENDIDIKAN YANG TERKANDUNG DALAM IBADAH SHOLAT - Heriyansyah Heriyansyah (Edukasi Islami: Jurnal Pendidikan Islam, 2015)
Prayer Is the Supreme Act of worship in islam and have a lot of wisdom in it. Pray that Allah enjoined in unto his servants who commissioned directly without going through intermediaries with the road to heaven servant up to sidrotul muntaha, prayers that are the poles of Islamic religion, whoever established it means he has founded the religion and whoever left it means he has destroyed his religion. Prayer in islam pillars occupy a second witness that there is no God in worship besides Allah and Prophet Muhammad as his Messenger and servant, as well as prayer becomes a comparison between faith and infidelity.Â  Even so, many of the Islamic society at this moment feels less notice in the matter of prayer, especially in the implementation of the required prayers five times a day last night. We witnessed many Mosque-the mosque which feels deserted from performing a go, perhaps many of the Islamic society at the time.Â Key Word: sholat, Ibadah, Nilai